Ketepatan Ekspektasi Telemarketing di Bank Portugal: Memanfaatkan Penambangan Data - irfan abbas; Asriani; Faisal Binsar; Abdul Halik (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
Banks play a basic role in economic improvement as well as contribute various cash related organizations to clients. Telemarketing is a commonly applied exchange method inside banks to offer and develop unused organizations to their clients. This kind of campaign generates a vast collection of data, A suitable examination of this data can support banks in organizing future strategies. Furthermore, it considera proposed data mining approach, to analyze and predict using atelemarketing campaign dataset. This dataset is composed based on demonstration pieces collected from clients, amid live call sessions organized by the bank. To execute the proposed view. The results show that the calculated backslide gives the best precision among the three models, recorded at 91.48%.